Orientation matters: Measuring the correct surface of polyamide membranes with quartz crystal microbalance - Luis Francisco Villalobos; Kevin E. Pataroque; Weiyi Pan; Tianchi Cao; Masashi Kaneda; Camille Violet; Cody L. Ritt; Eric M.V. Hoek; Menachem Elimelech (Journal of Membrane Science Letters, 2023)
The surface of polyamide reverse osmosis (RO) membranes which regulates interface-dominated phenomena, such as partitioning and fouling, is the one facing the feed during operation. However, the opposite surface of the polyamide selective layer, the one facing the permeate and in contact with the polysulfone porous support, is commonly analyzed in quartz crystal microbalance (QCM) measurements due to limitations of state-of-the-art transfer methodologies. Such measurements on the back surface cannot be generalized because the polyamide layer is chemically and morphologically asymmetric. Herein, we introduce a simple method to coat QCM sensors with polyamide active layers in the correct orientation (i.e., exposing their front surface) and show that interface-dominated phenomena differ significantly between orientations. We start by describing a transfer protocol to coat any surface with a polyamide layer on its front surface orientation. We then systematically analyze the chemical and morphological differences between the two surfaces of the polyamide layer of a commercial RO membrane. Finally, we demonstrate that interface-dominated phenomena depend on the orientation by showing that NaCl partitioning at pH 6 was 1.3 to 2.3-fold higher on the front surface and that organic fouling with humic acid occurred at a lower rate on this surface. The new method presented herein enables measurements on the front surface of polyamide RO membranes, which should be the standard in any future QCM studies.